Limited synergy of obesity and hypertension, prevalent risk factors in onset and progression of heart failure with preserved ejection fraction. Issue 10 (31st July 2019) - Brandt, Maarten M.; Nguyen, Isabel T. N.; Krebber, Merle M.; van de Wouw, Jens; Mokry, Michal; Cramer, Maarten J.; Duncker, Dirk J.; Verhaar, Marianne C.; Joles, Jaap A.; Cheng, Caroline
Abstract: Obesity and hypertension are prevalent comorbidities in heart failure with preserved ejection fraction. To clarify if and how interaction between these comorbidities contributes to development of diastolic dysfunction, lean and obese ZSF1 rats were treated with deoxycorticosterone acetate implants and a high‐salt diet (DS) to induce severe hypertension, or with placebo. In addition to echocardiographic, metabolic and hemodynamic analyses, immunohistochemistry and RNAseq were performed on left ventricular tissue. Obesity negatively affected cardiac output, led to an elevated E/e' ratio and mildly reduced ejection fraction. DS‐induced hypertension did not affect cardiac output and minimally elevated E/e' ratio. Diastolic derangements in placebo‐treated obese rats developed in absence of inflammation and fibrosis, yet in presence of oxidative stress and hypertrophic remodelling. In contrast, hypertension triggered apoptosis, inflammation and fibrosis, with limited synergy of the comorbidities observed for inflammation and fibrosis. Transcriptional data suggested that these comorbidities exerted opposite effects on mitochondrial function. In placebo‐treated obese rats, genes involved in fatty acid metabolism were up‐regulated, whereas DS‐induced a down‐regulation of genes involved in oxidative phosphorylation. Overall, limited interaction was observed between these comorbidities in development of diastolic dysfunction. Importantly, differences in obesity‐ and hypertension‐induced cardiac remodelling emphasize the necessity for comorbidity‐specific phenotypical characterization.